2020
DOI: 10.1038/s41467-020-15749-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen limitation reveals large reserves in metabolic and translational capacities of yeast

Abstract: Cells maintain reserves in their metabolic and translational capacities as a strategy to quickly respond to changing environments. Here we quantify these reserves by stepwise reducing nitrogen availability in yeast steady-state chemostat cultures, imposing severe restrictions on total cellular protein and transcript content. Combining multi-omics analysis with metabolic modeling, we find that seven metabolic superpathways maintain >50% metabolic capacity in reserve, with glucose metabolism maintaining >80% res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 55 publications
6
84
0
Order By: Relevance
“…Genes demonstrating the strongest uncoupling of transcription and translation as two distinct points of regulation-i.e. genes whose transcript and protein abundances were poorly correlated -were particularly enriched for CCM processes, consistent with previous indications that this central metabolic pathway is regulated by complex mechanisms to ensure robust output (8). We further showed that protein abundance is unlikely to be controlled by relative mRNA abundance, in line with recent large-scale proteomics studies showing that the organizing principle of the cell proteome can be substantially different from that of the transcriptome (43).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Genes demonstrating the strongest uncoupling of transcription and translation as two distinct points of regulation-i.e. genes whose transcript and protein abundances were poorly correlated -were particularly enriched for CCM processes, consistent with previous indications that this central metabolic pathway is regulated by complex mechanisms to ensure robust output (8). We further showed that protein abundance is unlikely to be controlled by relative mRNA abundance, in line with recent large-scale proteomics studies showing that the organizing principle of the cell proteome can be substantially different from that of the transcriptome (43).…”
Section: Discussionsupporting
confidence: 89%
“…Previously we have shown that the cell growth rate determines the allocation of the proteome and transcriptome to different processes, including the relative abundance of RNA polymerases and ribosomes (8,21). Our results here indicate that these growth rate-dependent changes in the transcription and translation machineries directly influences the absolute abundance ~90% of genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the transcriptome is remodeled in a global manner but at a smaller scale, while the proteome changes in a more specific manner that precisely impacts bioprocesses related to protein production, including amino acid transport, vitamin metabolism, protein modification, protein phosphorylation, and so on. The differences between transcriptome and proteome showed the reserves in translational capacity of yeast ( 18 ). Hence, we focused our analysis on differential expression at the proteome level between the three α-amylase production strains.…”
Section: Resultsmentioning
confidence: 99%